Matera building stones: Comparison between bioclastic and lithoclastic calcarenites - Bonomo, Agnese Emanuela; Lezzerini, Marco; Prosser, Giacomo; Munnecke, Axel; Koch, Roman; Rizzo, Giovanna (Building Materials, Materials Design and Applications, 2019)
Matera (Basilicata, southern Italy) was awarded World Heritage Site status by the UNESCO since 1993, and it will be the European Capital of Culture in 2019. It is one of the most ancient towns in the world, whose historical centre was totally built by only a moderately lithified and highly porous sedimentary building stone, known as Gravina Calcarenite. This easily workable rock was quarried since prehistoric times, and it was used for building different kind of constructions from the rupestrian settlement to the gorgeous historic palace during the XVIII century. Calcarenite, however, can be an extremely heterogeneous building material depending on the composition of the particles and their characteristics. After a geological survey, it was possible to recognize two main varieties of this building stone, which were in turn subdivided into six sub-typologies. As a first approach, we have characterized, in terms of building stone quality, the two main varieties: the bioclastic calcarenite and the lithoclastic calcarenite, sampled in the quarrying area to the North of Matera. The bioclastic calcarenite is from a new quarry in the upper part of the Calcarenite Formation, while the lithoclastic calcarenite is from an old quarry, inactive since 1965, in the lower part of the same formation. Mineralogical, petrographic and petrophysical tests have been carried out according to European Standards rules to highlight the main characteristics of different calcarenite types when used as building stone. Despite of their compositional differences, the bioclastic and lithoclastic calcarenite are both pure limestones with slightly different amounts of non-carbonates (silt quartz, clay minerals). The slightly different but characteristic mechanical properties clearly characterize the primary influence of grain composition, early cementation and micrite contents.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Building stone; Italian Unesco site; Petrographic characterization; Physical and mechanical properties